Development of Nanoemulsion containing essential oil of garlic (Allium Sativum) As pesticide formulation - Zakaria, Zulaika (2018)
This study is aimed to prepare an essential oil of Allium sativum and nanoemulsion, to characterize the nanoemulsion containing essential oils of Allium sativum and to determine the effectiveness of Allium sativum as the natural pesticide. The essential oil of Allium sativum was obtained through many processes such as hydrodistillation. The nanoemulsion was generate using polysorbate 80, glycerol, soybean oil, essential oils of garlic and water. The validity of the nanoemulsion was tested through many methods such as physical appearance, Tyndall effect, FTIR-ATR and DLS. DLS used to find the mean size of the particles. The mean of particle size of nanoemulsion is 118.89 nm while the mean of particle size of nanoemulsion containing garlic is 21.63 nm. The nanoemulsion containing garlic essential oil was tested on the ants through bioassay test. The results shows that the nanoemulsion containing garlic essential oil has less potential to use as pesticide. However, this is maybe due to the unfavourable conditions for the ants or any other errors which is need further studies.